Bilateral Chronic Subdural Hematoma and Blindness: Bilateral Infarction to the Posterior Cerebral Artery following Evacuation of Bilateral Chronic Subdural Hematoma — A Rare Case Report and Review of Literature - Balasubramanian, Sneha Chitra; Adimoolam, Sendilkumar; Shunmugam, Syamala (Indian Journal of Neurotrauma, 2017)
Objective The authors report a rare scenario in which evacuation of bilateral chronic subdural hematoma (CSDH) was followed by bilateral PCA infarction and blindness. A literature review was also conducted, which revealed only four cases of blindness after CSDH evacuation.Methods A 45-year-old man was admitted with the chief complaint of holocranial headache for 2 months with past history of head trauma. Clinical examination was normal. CT and MRI scanning showed bilateral frontotemperoparietal CSDH without midline shift and parenchymal and vascular abnormality. Bilateral frontal and parietal burr holes and evacuation of CSDH was done.Results The patient developed progressive blindness in both the eyes in the postoperative period. MRI revealed bilateral PCA infarction. Discussion Bilateral PCA infarction following bilateral CSDH evacuation is an extremely rare entity. Only four case of blindness following CSDH evacuation have been reported so far, and all the patients suffered permanent visual loss. The exact etiopathogenesis and mechanism of this rare complication remain unknown.Conclusion Bilateral CSDH is a separate entity with altered pathophysiology and deranged cerebral autoregulation. The authors conclude that Bilateral CSDH may be sentinel tags for bilateral PCA infarction secondary to altered hemodynamics in the posterior circulation, and hence, needs to be evaluated and treated with greater diligence.
Keywords: bilateral CSDH; bilateral PCA infarction; postoperative cortical blindness